STUDY OF THE IN-VITRO METABOLIC PROFILE OF AMLODIPINE IN HUMAN HEPATIC CELL LINE AND CHICKEN LIVER TISSUE USING LIQUID CHROMATOGRAPHY-MASS SPECTROMETRY/MASS SPECTROMETRY - Saxena, Divya; Damale, Shailesh; Datar, Ajit (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The main objective of this study was to investigate the in-vitro metabolic profile of Amlodipine (AMD) using normal human hepatic cell lines and chicken liver tissue and to characterize the metabolites obtained using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Methods: In the present study, the metabolic profile of AMD, a well-known calcium channel blocker, was investigated in normal human hepatic cell lines and chicken liver tissue employing LC-MS/MS technique. The structural details on AMD metabolites were acquired using triple quadrupole mass spectrometer (LCMS-8040, Shimadzu). The metabolites were produced by incubation of AMD with the human hepatic cell lines and chicken liver tissue at 37 Â°C for 24 h. The incubated extracts were analyzed on LC-MS/MS and their product ion spectra were acquired, interpreted and tentative structures were proposed. Results: Twelve Phase I and Phase II metabolites were successfully detected in the proposed study. The main metabolic changes observed were oxidative deamination, N-acetylation, de-esterification, hydrogenation, de-methylation, aliphatic hydroxylation, and glucuronidation of dehydrogenated AMD. Based on this information, the tentative structures of the metabolites were postulated. Conclusion: The in-vitro metabolites of AMD were successfully investigated and characterized in human hepatic cell lines and chicken liver tissue. Furthermore, both models were found to be equally effective for carrying out the in-vitro metabolic study of AMD. Keywords: Amlodipine, Metabolites, Hepatic cell lines, Chicken liver tissue, Liquid chromatography, Liquid chromatography-mass spectrometry/ mass spectrometry.